Sustainable Development Affecting by the Climate Change: A Secondary Study of Cyclones (Natural Disasters: Sidr, Aila and Roanu in Bangladesh) - Ruhullah, Mohammad Eisa; Purnomo, Eko Priyo; Malawani, Ajree D (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Climate change makes the world thoughtful to take care of nature to keep safe the earth. Bangladesh is one of the most popular countries that experienced many natural disasters almost every year. The aim of this research to make a measure of the factors that affected sustainable development in the country. By natural disasters cyclones such as Sidr 2007, Aila 2009, and Roanu 2016, which will help the responsible division of the natural disaster and sustainable development sectors to figure out the knowledge about natural disasters that effecting the SDG in the country. The research shows the result that cyclone (Sidr 2007, Aila 2009, and Roanu 2016), flood, earthquake, and land-sliders are the most dangerous and frequent natural disasters that were affecting sustainable development. By the damages of the info structure in the country such as roads, houses, bridges, agriculture, cyclone centers, and social economy. Those problems can solve with the advancement of education plus providing the physical resources in advance to face the incident. Furthermore, natural disaster management works together with the United Nations Development Programs by implicating the Climate Change Assessment Projects in Bangladesh.